Hall-Petch strengthening in ultrafine-grained Zn with stabilized boundaries - Martin Balog; Peter Krížik; Andrea Školáková; Peter Švec; Jiří Kubásek; Jan Pinc; Moara Marques de Castro; Roberto Figueiredo (Journal of Materials Research and Technology)
A relationship between the tensile yield stress and grain size i.e., Hall-Petch (H–P) law, for an ultrafine-grained (UFG) Zn was experimentally evaluated for the first time. In reality, it is problematic to assess this prediction using experimental results due to the low recrystallization temperature of a pure Zn. In order to do so, three Zn bulk materials with the intercept grain size (dl) ranging from 0.6 to 1.1 μm, stabilized with a small portion of nanoscale ZnO dispersoids positioned at high angle grain boundaries (HAGB), were fabricated from fine pure Zn powders. The material with the finest grain size of 0.6 μm, ever reported for unalloyed Zn, also exhibited the highest ultimate tensile and 0.2% strain offset yield strengths (YS0.2), ever reported for unalloyed Zn. The strengths were accompanied by a reasonably high ductility. Deformation in the presented materials was attributed to the grain boundary sliding (GBS) mechanism. The experimental data were compared with a theoretical model of the deformation behavior of UFG metals based on GBS through dislocation glide. We confirmed, that the linear H–P relation YS0.2=40.8+104.8dl−0.5 remained in force in the range of dl = ∼400–0.6 μm. A grain refinement softening in UFG region predicted by the theoretical model and other experimental works was avoided. This was attributed to the presence and an effective stabilizing effect of the nano-metric ZnO at HAGB, which impeded GBS. The practical implications of the presented concept of Zn-based bioresorbable material are discussed from the point of view of potential applications in implantology.